Comparing 36.5°C with 37°C for human embryo culture: a prospective randomized controlled trial. Issue 6 (June 2018) - Fawzy, Mohamed; Emad, Mai; Gad, Mostafa A.; Sabry, Mohamed; Kasem, Hesham; Mahmoud, Manar; Bedaiwy, Mohamed A.
Abstract: This prospective, double-blind, randomized controlled trial was designed to evaluate the efficacy of a culture temperature of 36.5°C versus 37°C on human embryo development in vitro . A total of 412 women undergoing IVF were randomized to two groups: the oocytes and embryos of the intervention group were cultured at 36.5°C; those of the control group were cultured at 37°C. Although no significant effect of culture temperature was observed on pregnancy or implantation rates, differences were found in embryo development. Embryo culture at 36.5°C was associated with a significantly higher cleavage rate (OR 1.6, 95% CI 1.03 to 2.51), but a lower fertilization rate, fewer high-quality embryos on day 3, a lower blastocyst formation rate on day 5, and fewer high-quality and cryopreserved blastocysts (OR 0.87, 95% CI 0.78 to 0.98), (OR 0.60, 95% CI 0.53 to 0.69), (OR 0.85, 95% CI 0.75 to 0.97), (OR 0.5, 95% CI 0.44 to 0.56) and (OR 0.77, 95% CI 0.68 to 0.88), respectively, compared with 37°C. On the basis of these results, and in the absence of data on the optimal temperature for each stage of embryo development in vitro, we recommend continuation of the use of 37°C for human embryo culture.